FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA REMAJA PUTRI SMP ISTIQLAL DELITUA - Abdul Hairuddin Angkat; Fauzi Romeli; Emi Inayah; Wanda Lestari (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
One of the health problems that often occurs in adolescents, especially adolescent girls, is anemia. This is caused by a lack of nutritional intake that affects the nutritional status of adolescents. Anemia is a condition in which hemoglobin and erythrocyte levels are lower than normal. The purpose of this study was to determine the factors associated with the incidence of anemia in adolescent girls at Istiqlal Delitua Junior High School. This research was conducted at Istiqlal Delitua Junior High School. The research was conducted in January 2024. Type of quantitative research with cross-sectional design. The population of adolescent girls in classes VII and VIII amounted to 51 students with a sample of 37 students. The sample technique used simple random sampling. The research instrument was a questionnaire and Hb checker (Easy Touch GCHb). Data analysis is univariate, bivariate and multivariate. The results showed that there was a relationship between breakfast habits and the incidence of anemia in adolescent girls obtained p=0.022 < (0.05), the relationship between nutritional knowledge and the incidence of anemia in adolescent girls in adolescent girls obtained p=0.002 < (0.05), and the relationship between gadget use activities with the incidence of anemia in adolescent girls obtained p=0.034 < (0.05). Based on the final model of multivariate analysis, the variable that has the greatest influence on the incidence of anemia is the breakfast variable.